Implementasi Algoritma Random Forest Dalam Menentukan Kualitas Susu Sapi - Paramaditya, I Putu Ryan; Paramartha, Cokorda Rai Adi (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Milk is one of the food ingredients as a source of animal protein that can meet the needs and improve the nutrition of the people of Indonesia, especially protein, carbohydrates, fats and minerals of high nutritional value, namely calcium and phosphorus which can help the healing process of various diseases. Use the classification method performed with the Random Forest algorithm on the data content of cow's milk content where the results of the experiments that have been carried out, the accuracy rate of classification with the Random Forest algorithm is 98%. In addition, in testing precision, recall, and f1-score generated from each variable has the same value of 98%. then the highest level of accuracy of the response variable is in the "medium" category.